2018
DOI: 10.1371/journal.pone.0191683
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of inhibitory effects of bovine lactoferrin on the growth of oral squamous cell carcinoma

Abstract: BackgroundLactoferrin (LF), a member of the transferrin family, recently has been demonstrated to have anticancer effects on various cancers including oral squamous cell carcinoma (OSCC). However, little is known about the underlying mechanisms of its effects on OSCC. Therefore, we aimed to investigate the mechanism of the suppressive effects of bovine LF (bLF) on the growth of OSCC cells.MethodsIn the current study, HSC2, HSC3, HSC4 and normal human oral keratinocytes (RT7) cell lines were tested with bLF 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 57 publications
2
28
1
7
Order By: Relevance
“…Compared with the control, the proportion of cells at G2/M phase increased in both free bLF and its conjugated form; but, the effect of CGO-PEG-bLF in arresting the cells was significantly higher than that of free bLF. Despite our results, several reports have demonstrated that bLF arrested the cell cycle in the G1/S phase in some types of cancers (Zhou et al., 2008 ; Xu et al., 2010 ; Chea et al., 2018 ). Induction of cell cycle arrest at the G2/M phase in MDA-MB-231 and T-47D cells has been reported by Zhang et al.…”
Section: Resultscontrasting
confidence: 95%
See 2 more Smart Citations
“…Compared with the control, the proportion of cells at G2/M phase increased in both free bLF and its conjugated form; but, the effect of CGO-PEG-bLF in arresting the cells was significantly higher than that of free bLF. Despite our results, several reports have demonstrated that bLF arrested the cell cycle in the G1/S phase in some types of cancers (Zhou et al., 2008 ; Xu et al., 2010 ; Chea et al., 2018 ). Induction of cell cycle arrest at the G2/M phase in MDA-MB-231 and T-47D cells has been reported by Zhang et al.…”
Section: Resultscontrasting
confidence: 95%
“…Although, other proteins may be involved in this process. Similar results regarding effect of bLF on the three cell lines of oral squamous cell carcinoma (HSC1, HSC2, HSC3) have been reported by Chea et al (Chea et al., 2018 ). Their findings indicated that bLF downregulated the phosphorylation of AKT and upregulated the cleaved-caspase 3 protein selectively in HSC3 cells but not in RT7 (normal human oral keratinocytes).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In line with these studies, Chea et al [145] showed that bLf was able to induce cell cycle arrest also in a model of oral squamous cell carcinoma by increasing levels of both phospho-p53 and CdK inhibitor p21 and decreasing the expression of cyclin D1, a regulator protein required for progression through G1 phase of cell cycle. Importantly, bLf neither down-regulated phospho-p53 and cyclin D1 nor up-regulated p21 levels in RT7 cells, a normal human oral keratinocytes line [145].…”
Section: Lactoferrin Anti-cancer Activity: Modulation Of Cell Cyclementioning
confidence: 77%
“… [ 69 ] OSCC bLf Selective suppression of growth through mTOR/S6K & JAK/STAT3 signaling pathways and triggering of apoptosis in OSCC. [ 70 ] Head & Neck Recombinant hLf LF induced growth inhibitory effects via p27/cyclin E-dependent signaling pathway by regulating Akt phosphorylation. [ 71 ] GBM hLf Suppression of the proliferation of NMD and FN primary cells as well as U87MG cells by reducing the expression of cyclin D1 and D4.…”
Section: Pharmacological Activities Of Lactoferrinmentioning
confidence: 99%